Improvement in disease severity and pruritus outcomes with crisaborole ointment, 2%, by baseline atopic dermatitis severity in children and adolescents with mild‐to‐moderate atopic dermatitis. Issue 6 (27th September 2020) - Eichenfield, Lawrence F.; Yosipovitch, Gil; Stein Gold, Linda F.; Kalabis, Mizuho; Zang, Chuanbo; Vlahos, Bonnie; Sanders, Paul; Myers, Daniela E.; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Olivadoti, Melissa; Paller, Amy S.
Abstract: Background/Objectives: Crisaborole ointment, 2%, is a nonsteroidal phosphodiesterase 4 inhibitor for the treatment of mild‐to‐moderate atopic dermatitis (AD). This pooled post hoc analysis of two phase 3 trials (NCT02118766, NCT02118792) assessed improvement and time to improvement in Investigator's Static Global Assessment (ISGA) and Severity of Pruritus Scale (SPS) outcomes in pediatric patients with mild‐to‐moderate AD. Methods: Patients aged ≥2 years were randomly assigned 2:1 to receive twice‐daily crisaborole or vehicle for 28 days. Patients aged 2‐17 years were pooled for this analysis. Proportions of patients and time to achieving ISGA success (clear [0] or almost clear [1] with ≥2‐grade improvement from baseline), ISGA clear/almost clear, ≥1‐grade improvement in ISGA, SPS success (SPS score ≤1 with ≥1‐grade improvement), or ≥1‐grade improvement in SPS score were analyzed and stratified by baseline ISGA. Results: At first postbaseline assessment (day 8), significantly higher proportions of crisaborole‐ than vehicle‐treated patients achieved ISGA success, ISGA clear/almost clear, ≥1‐grade ISGA improvement, SPS success, or ≥1‐grade improvement in SPS regardless of baseline ISGA. Differences were significantly greater over time for all outcomes for patients with moderate baseline ISGA and numerically greater for those with mild baseline ISGA. Median times to ISGA and SPS outcomes were shorter for crisaborole versus vehicle. Conclusion: Improvement in ISGA and SPS outcomes were observed with crisaborole in pediatric patients with mild‐to‐moderate baseline AD.